Design And Construction Of Power Plant Coconut Shells As A Power Supply On Lighting Lamps - Damanik, Samuel Valentino; Simanjuntak, Rossi Peter; Aulia, Rahman; N, Susi Diriyanti (STABN RADEN WIJAYA WONOGIRI, 2024)
The management of coconut shell waste is one of the environmental challenges that requires appropriate solutions. The growing energy demand in line with population growth drives the need for innovative renewable energy–based solutions. One alternative that can be applied is the utilization of Thermoelectric Generator (TEG) technology based on the Seebeck effect in a Biomass Power Plant (PLTBm) system. This study aims to design and develop an electricity generation system that harnesses heat energy from the combustion of coconut shells to produce electrical power for lighting lamps. The research employed a descriptive quantitative method to explain a process or phenomenon without correlating it to other variables. The energy conversion process was carried out using six TEG units connected in series to maximize voltage output. The generated voltage was then regulated and stored in a battery via a Solar Charge Controller (SCC), and monitored using an INA219 sensor connected to an Arduino UNO microcontroller. The experimental results showed that a temperature difference (∆T) of 227.7°C between the hot and cold sides of the TEG produced a maximum voltage of 15.87 volts. This system was proven to monitor TEG performance in real time and provide a reliable power supply for lighting, offering an alternative renewable energy solution utilizing coconut shell waste.